2005
DOI: 10.1207/s15327957pspr0902_3
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Expectations and Self-Fulfilling Prophecies: Knowns and Unknowns, Resolved and Unresolved Controversies

Abstract: This article shows that 35 years of empirical research on teacher expectations justifies the following conclusions: (a) Self-fulfilling prophecies in the classroom do occur, but these effects are typically small, they do not accumulate greatly across perceivers or over time, and they may be more likely to dissipate than accumulate; (b) powerful self-fulfilling prophecies may selectively occur among students from stigmatized social groups; (c) whether self-fulfilling prophecies affect intelligence, and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
637
4
29

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 898 publications
(694 citation statements)
references
References 70 publications
24
637
4
29
Order By: Relevance
“…This phenomenon became known as the self-fulfilling prophecy, as originally defined by Merton (1948). Many researchers have investigated the self-fulfilling prophecy effect of teacher expectations on future performance of students in both naturalistic and experimental settings, concluding that self-fulfilling prophecies generally seem to have only relatively small effects on student achievement (Jussim and Harber 2005;RubieDavies 2008). In this research tradition the term ''teacher expectations'' refers to inferences made by teachers with respect to students' potential to achieve based on the teachers' current knowledge about these students (Good 1987;Riley and Ungerleider 2012).…”
Section: Teacher Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon became known as the self-fulfilling prophecy, as originally defined by Merton (1948). Many researchers have investigated the self-fulfilling prophecy effect of teacher expectations on future performance of students in both naturalistic and experimental settings, concluding that self-fulfilling prophecies generally seem to have only relatively small effects on student achievement (Jussim and Harber 2005;RubieDavies 2008). In this research tradition the term ''teacher expectations'' refers to inferences made by teachers with respect to students' potential to achieve based on the teachers' current knowledge about these students (Good 1987;Riley and Ungerleider 2012).…”
Section: Teacher Expectationsmentioning
confidence: 99%
“…Studies focusing on naturally occurring differential teacher expectations for demographic characteristics of students and their families have thus far resulted in inconsistent findings (Alvridez and Weinstein 1999;McKown and Weinstein 2008). In their review, Jussim and Harber (2005) conclude that teachers are not biased because the differences in teacher expectations for stigmatized demographic student subgroups closely correspond to differences in those groups' academic performance in previous grades and achievement tests. However, a substantial number of studies published after Jussim and Harber's (2005) review have found significant differences in teacher expectations for students of different demographic groups after the previous performance of students was controlled for (e.g., Glock and Krolak-Schwerdt 2013;McKown and Weinstein 2008;Rubie-Davies et al 2006;Speybroeck et al 2012;Tenenbaum and Ruck 2007;van den Bergh et al 2010).…”
Section: Teacher Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examine the formation of public school teachers' expectations of student educational attainment. Teachers likely play an important role in shaping students' beliefs about their academic prospects (Burgess & Greaves, 2013;Dee, 2015), particularly among relatively disadvantaged students who rarely interact with collegeeducated adults outside of school settings (Jussim & Harber, 2005;Lareau & Weininger, 2008;Lareau, 2011). More concerning, teachers' beliefs can affect students' performance.…”
Section: Introductionmentioning
confidence: 99%
“…This body of evidence is drawn from research on teacher expectancy effects (for review see Jussim & Harber, 2005), classroom goal structure (for review see Urdan & Midgley, 2003), classroom task structures (Simpson & Rosenholtz, 1986), and teacher frame of reference (Marsh & Craven, 2002). The literature from these separate but overlapping traditions has identified teacher practices that are associated with the self-fulfilling prophesy effect (Rosenthal & Jacobson, 1968) and with students' academic motivation and perceived competence (Dweck & Leggett, 1988;Lüdtke, Köller, Marsh, & Trautwein, 2005;Urdan, Midgley, & Anderman, 1998).…”
Section: Introductionmentioning
confidence: 99%